AIDS & HIV in perspective : a guide to understanding the virus and its consequences - Schoub, B. D. (Cambridge University Press, 1999)
"A new edition of Professor Schoub's lucid and informative account brings the reader up to date on the major advances in our current understanding of HIV infection and its control. This book uses clear language and helpful diagrams to explain the basic biology of the HIV virus, and of the immune system that it so lethally undermines. It aims explicitly to bridge the gap between the vast scientific literature and the wide range of educational materials now available to the public."--Jacket